Respuesta :

Answer:

(3x-5)(x+2)

Step-by-step explanation:

Answer:

(x + 2)(3x - 5)

Step-by-step explanation:

Given

3x² + x - 10

Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term.

product = 3 × - 10 = - 30 and sum = + 1

The factors are + 6 and - 5

Use these factors to split the x- term

3x² + 6x - 5x - 10 ← factor by grouping first/second and third/fourth terms

= 3x(x + 2) - 5(x + 2) ← factor out (x + 2) from each term

= (x + 2)(3x - 5)

ACCESS MORE